Be proactive, collaborate to address mental health threats. Issue 11 (March 2016) - Hope, Joan
Abstract : Since the mass shootings at Virginia Polytechnic Institute and State University, campus safety officials across the country have given a lot of thought to preventing similar tragedies. The Virginia Tech shooter had clear mental health issues. Officials missed the warning signs because people on campus weren't talking to each other, said Cheryl Newman‐Tarwater, captain of the Community College Bureau for the Los Angeles County Sheriff's Department. Her unit provides public safety services for the Los Angeles Community College District.